2018
DOI: 10.1016/j.celrep.2018.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutational Landscape of Splicing Factor Genes and Their Functional Consequences across 33 Cancer Types

Abstract: SUMMARY Hotspot mutations in splicing factor genes have been recently reported at high frequency in hematological malignancies, suggesting the importance of RNA splicing in cancer. We analyzed whole-exome sequencing data across 33 tumor types in The Cancer Genome Atlas (TCGA), and we identified 119 splicing factor genes with significant non-silent mutation patterns, including mutation over-representation, recurrent loss of function (tumor suppressor-like), or hotspot mutation profile (oncogene-like). Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
321
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 365 publications
(336 citation statements)
references
References 67 publications
13
321
0
2
Order By: Relevance
“…The expression of WEE1 is suppressed in colon cancer and non‐small cell lung cancer . Interestingly, the expression of some tumor suppressor genes, such as LKB1 and KLF6 , was controlled by splicing alterations . In the present study, we showed that WEE1 expression is also altered through alternative splicing by DDX56 overexpression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The expression of WEE1 is suppressed in colon cancer and non‐small cell lung cancer . Interestingly, the expression of some tumor suppressor genes, such as LKB1 and KLF6 , was controlled by splicing alterations . In the present study, we showed that WEE1 expression is also altered through alternative splicing by DDX56 overexpression.…”
Section: Discussionsupporting
confidence: 54%
“…RNA splicing enables the production of multiple mRNA species by alternative splicing of exons, which are found in nearly 95% of mammalian genes, to generate tissue‐ and species‐specific differentiation patterns . Deregulated or abnormal splicing is often observed in various malignancies, including colorectal cancer (CRC), which is one of the most common malignant tumors worldwide . Furthermore, splicing abnormality has recently been recognized as an important mechanism for regulating the expression of cancer‐related genes …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to mediate the alternative splicing of multiple genes involved in different cancer‐related processes, such as the epithelial to mesenchymal transition and resistance to therapy . Recent reports have shown that the activity of alternative splicing regulators is recurrently altered in cancer, and this affects transcripts balance of key genes involved in cancer‐related pathways …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an M110I mutation corresponding to the n5127 M157I mutation in C. elegans UAF-1 [35] was identified in a case of uterine corpus endometrial carcinoma. Mutations in the U2AF large subunit gene and the splicing factor one gene ( sfa-1 ) have also been proposed to be potential cancer drivers based on a comprehensive analysis of the mutation profiles of over 400 splicing factors in various cancers [65]. …”
Section: Discussionmentioning
confidence: 99%